FSFS Neotherian and Artinian Modules - Alhusini , Amjad Hamead; Althabhawi, Sami Kadhem (Iraqi Journal of Science, 2023)
Letbe anmodule,be a fuzzy soft module over, andbe a fuzzy soft ring over, thenis called FSFS module if and only ifis anmodule. In this paper, we introduce the concept ofNoetherian andArtinian modules and finally we investigate some basic properties ofNoetherian andArtinian modules.